Effect of Pressure on the Properties of HgBa2Ca2Cu3O8+δ HTSC System - Hermiz, G. Y. (Iraqi Journal of Physics, 2008)
High temperature superconductors with a nominal composition HgBa2Ca2Cu3O8+δfor different values of pressure (0.2,0.3, 0.5, 0.6, 0.9, 1.0 & 1.1)GPa were prepared bya solid state reaction method. It has been found that the samples were semiconductorP=0.2GPa.while the behavior of the other samples are superconductor in the rang(80-300) K. Also the transition temperature Tc=143K is the maximum at P is equal to0.5GPa. X-ray diffraction showed a tetragonal structure with the decreasing of thelattice constant c with the increasing of the pressure. Also we found an increasing ofthe density with the pressure.